Pengaruh Model Problem Based Learning dengan Menggunakan Media Puzzle Terhadap Hasil Belajar Peserta Dididk pada Pokok Bahasan Sistem Peredaran Darah Kelas XI di SMA Negeri 2 Tondano - Palapa, Tommy M; Rayer, Debby J.J; Pasolon, Angelina Wiwi (JSME (Jurnal Sains, Matematika & Edukasi), 2020)
The teaching and learning process with the use of media and learning models has not been maximized. The activeness of students during the learning process is still lacking, students have not been trained to find solutions to solve problems, students are indifferent to the subject matter delivered by the teacher. This studied aims to determine the effect of differences in Problem Based Learning models by using media Puzzles on learning outcomes of students on the subject of the circulatory system of class XI in SMA Negeri 2 Tondano in the academic year 2019/2020. This type of research is experimental research. The sample used in this study is class XI IPA 1 consisting of 22 students as the control class and XI IPA 2 consisting of 22 students as the experimental class. Data collection techniques using learning outcomes tests with test instruments in the form of multiple choice questions. The results showed that the average experimental class learning outcomes = 82.04 while the average control class learning outcomes = 62.72. ata were analyzed using the T-test statistic at a significance level of 0.05 and the results obtained were Tcount = 9.41> Ttable = 2.02. From these results it can be concluded that there is a difference in the Problem Based Modeling Learning Model using the media of Puzzles on student learning outcomes.Â Keywords: learning outcomes, puzzle media, problem based learning